Motion deblurring : algorithms and systems - Rajagopalan, A. N.; Chellappa, Rama (Cambridge : Cambridge University Press, 2014)
A comprehensive guide to restoring images degraded by motion blur, bridging the traditional approaches and emerging computational photography-based techniques, and bringing together a wide range of methods emerging from basic theory as well as cutting-edge research. It encompasses both algorithms and architectures, providing detailed coverage of practical techniques by leading researchers. From an algorithms perspective, blind and non-blind approaches are discussed, including the use of single or multiple images; projective motion blur model; image priors and parametric models; high dynamic range imaging in the irradiance domain; and image recognition in blur. Performance limits for motion deblurring cameras are also presented. From a systems perspective, hybrid frameworks combining low-resolution-high-speed and high-resolution-low-speed cameras are described, along with the use of inertial sensors and coded exposure cameras. Also covered is an architecture exploiting compressive sensing for video recovery. A valuable resource for researchers and practitioners in computer vision, image processing, and related fields.
Contents note continued: 4.3. The computational model -- 4.4. Blind estimation of blur from a single image -- 4.5. Efficient computation of the spatially-variant model -- 4.6. Single-image deblurring results -- 4.7. Implementation -- 4.8. Conclusion -- 5. Removing camera shake in smartphones without hardware stabilization / Jan Flusser -- 5.1. Introduction -- 5.2. Image acquisition model -- 5.3. Inverse problem -- 5.4. Pinhole camera model -- 5.5. Smartphone application -- 5.6. Evaluation -- 5.7. Conclusions -- 6. Multi-sensor fusion for motion deblurring / Jlngyi Yu -- 6.1. Introduction -- 6.2. Hybrid-speed sensor -- 6.3. Motion deblurring -- 6.4. Depth map super-resolution -- 6.5. Extensions to low-light imaging -- 6.6. Discussion and summary -- 7. Motion deblurring using fluttered shutter / Amit Agrawal -- 7.1. Related work -- 7.2. Coded exposure photography -- 7.3. Image deconvolution -- 7.4. Code selection -- 7.5. Linear solution for deblurring -- 7.6. Resolution enhancement.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Image processing -- Mathematics; Image processing -- Digital techniques; Digital video -- Editing -- Mathematics; Photography -- Retouching -- Data processing; Motion -- Mathematical models